Inovasi Teknologi Pendidikan Melalui Podcast Sebagai Suplemen Pembelajaran di Sekolah (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2022)
Digital podcasts (audio/video) can be a new innovation for learning development, especially at the school education level. Teachers and students can take advantage of audio podcasts as a learning tool in schools. This research was conducted at SMA Plus Darussalam Ciamis using a descriptive method. Data collection techniques using interviews, observation and documentation. The results show that digital podcasts can be used as a medium of learning at SMA Plus Darussalam Ciamis. In addition to its contents regarding learning information, there is other information such as general knowledge about Islamic boarding schools, etc., because SMA Plus Darussalam is under the Darussalam Ciamis Islamic Boarding School.